New Insights into the Binding Mechanism of Co-regulator BUD31 to AR AF2 Site: Structural Determination and Analysis of the Mutation Effect - Song, Tianqing; Li, Jiazhong (Current Computer - Aided Drug Design, 2020)
Introduction: Androgen Receptor (AR) plays a pivotal role in the development of male sex and contributes to prostate cancer growth. Different from other nuclear receptors that bind to the co-regulator LxxLL motif in coregulator peptide interaction, the AR Ligand Binding Domain (LBD) prefers to bind to the FxxLF motif. BUD31, a novel co-regulator with FxxLF motif, has been demonstrated to suppress wild-type and mutated AR-mediated prostate cancer growth. Methods: To find out the interaction mechanisms of BUD31 with WT/T877A/W741L AR complex, molecular dynamics simulations were employed to study the complex BUD31 and WT/mutant ARs. The molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) results demonstrated that T877A and W741L point mutations can reduce the binding affinity between BUD31 and AR. The RMSF and dynamic cross-correlation analysis indicated that amino acid point mutations can affect the motions of loop residues in the AR structure. Results: These results indicated that AR co-regulator binding site AF2 can serve as a target for drug discovery to solve the resistance problem.
Keywords: interaction mechanism